Pilot model of the rehabilitating treatment of self-esteem and behavior in adolescents with dyslexia and dysortography through their literate improvement - Zuppardo, Linda (2017)
Clinical and educational research has highlighted the emotional and motivational factors that characterize learning difficulties. The main objective of this research is to assess the effects of rehabilitative treatment on self-esteem and behavior in a group of patients diagnosed with dyslexia and dysortography. To 60 students with a diagnosis of dyslexia, at first, they will be given a battery of tests, to assess the emotional and behavioral profile. Afterwards, the experimental group will undergo a rehabilitation treatment that aspires to enhance the performance in reading and writing. In summary, the results show that, through an adequate rehabilitation course with the support of adequate instruments, dyslexic patients can achieve greater self-confidence and a consequent greater self-esteem.